Co-infection with Campylobacter and rotavirus in less than 5 year old children with acute gastroenteritis in Nepal during 2017-2018 - Vishnu Bhattarai; Saroj Sharma; Komal Raj Rijal; Megha Raj Banjara (BMC, 2020)
Abstract Background Diarrhoea, although easily curable, is a global cause of death for a half million children every year. Rotavirus and Campylobacter are the most common etiological agents of diarrhoea in children less than 5 years of age. However, in Nepal, these causative agents are not routinely examined for the diagnosis and treatment. The main objective of this study was to determine Campylobacter co-infection associated with rotavirus diarrhoea in children less than 5 years of age. Methods A cross-sectional study was conducted at Kanti Children's Hospital (KCH), Kathmandu, Nepal from November 2017 to April 2018. A total of 303 stool specimens from children affected with diarrhoea were processed to detect rotavirus using a rapid rotavirus antigen detection test kit, and Campylobacter by microscopy, culture and biochemical tests. Antibiotic susceptibility tests of Campylobacter isolates were performed according to European Committee on Antimicrobial Susceptibility Testing (EUCAST) guidelines 2015. Results Of 303 samples, 91 (30.0%) were positive for co-infection with rotavirus and Campylobacter. Rotavirus mono-infection was detected in 61 (20.1%), and Campylobacter mono-infection was detected in 81 (26.7%) samples. Patient's age, month of infection, untreated water and frequent soil contact were the major risk factors for infections. Clinical features such as > 9 loose motions per day, fever, vomiting, mild to moderate dehydration, diarrhea persisting 6-9 days and presence of mucus in stool were significant (p < 0.05) clinical features, and were more severe in coinfection compared to mono-infections in multivariate analysis. Conclusion The study shows a high rate of rotavirus and Campylobacter coinfection in children with diarrhoea. Diagnosis based management of diarrhoeal cases can guide the specific treatment.